2017
DOI: 10.1002/jccs.201700024
|View full text |Cite
|
Sign up to set email alerts
|

Silver–N‐Heterocyclic Carbene Complexes: Synthesis, Characterization, and Antimicrobial Properties

Abstract: Six new silver complexes containing symmetrical N‐heterocyclic carbene (NHC) ligands were synthesized by the reaction of azolium salts with Ag2O in CH2Cl2 . These complexes were tested against Gram‐negative bacterial strains (Escherichia coli and Pseudomonas aeruginosa), Gram‐positive bacterial strains (Enterococcus faecalis and Staphylococcus aureus), and fungal strains (Candida albicans and Candida tropicalis), and all tested complexes showed good activity against the different microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Similar results were obtained with a benzimidazole‐based neutral silver NHC complex with benzodioxanyl and benzyl/4‐methylbenzyl substituents as reported by Sari et al [ 72 ] Similarly, Karataş et al [ 73 ] reported similar bis‐NHC coordinated silver(I) complexes which displayed good antibacterial activity (MIC in the range 50–200 MIC μg/ml against E. coli ). These values are comparable to other related results in the literature; in some cases, the complexes have shown better results, [ 72–74 ] indicating that these new Ag–NHC complexes are quite potent.…”
Section: Resultssupporting
confidence: 90%
“…Similar results were obtained with a benzimidazole‐based neutral silver NHC complex with benzodioxanyl and benzyl/4‐methylbenzyl substituents as reported by Sari et al [ 72 ] Similarly, Karataş et al [ 73 ] reported similar bis‐NHC coordinated silver(I) complexes which displayed good antibacterial activity (MIC in the range 50–200 MIC μg/ml against E. coli ). These values are comparable to other related results in the literature; in some cases, the complexes have shown better results, [ 72–74 ] indicating that these new Ag–NHC complexes are quite potent.…”
Section: Resultssupporting
confidence: 90%
“…These data are in agreement with those of the benzimidazolium salts previously reported in the literature. [ 55,66–71 ]…”
Section: Resultsmentioning
confidence: 99%
“…There are studies in the literature on the antimicrobial properties of benzimidazoliumderived Ag(I)-NHCs. Several bacteria and fungi isolates were used by Kaloğlu et al [13]. to evaluate the antimicrobial activities of the Ag-(I) NHC compounds they synthesized.…”
Section: Discussionmentioning
confidence: 99%